MicroRNAs and the neural crest: From induction to differentiation - Weiner, Andrea Maria Julia (2018)
MicroRNAs are small noncoding RNAs that can control gene expression by base pairing to partially complementary mRNAs. Regulation by microRNAs plays essential roles in diverse biological processes such as neural crest formation during embryonic development. The neural crest is a multipotent cell population that develops from the dorsal neural fold of vertebrate embryos in order to migrate extensively and differentiate into a variety of tissues. Gene regulatory networks that coordinate neural crest cell specification and differentiation have been considerably studied so far. Although it is known that microRNAs play important roles in neural crest development, posttranscriptional regulation by microRNAs has not been deeply characterized yet. This review is focused on the microRNAs identified so far in order to regulate gene expression of neural crest cells during vertebrate development.